Feasibility study of real-time three- dimensional intracardiac echocardiography for guidance of interventional electrophysiology. - Smith SW; Light ED; Idriss SF; Wolf PD (Pacing & Clinical Electrophysiology, 2002)
The authors tested the feasibility of real-time three-dimensional intracardiac echocardiography for guidance of interventional electrophysiological studies. The three-dimensional scanner uses a matrix array ultrasound transducer of 64 channels operating at 5 MHz in a 12 Fr catheter. The system features real-time three-dimensional image rendering and produces up to 60 volumetric scans per second. Using an open-chest sheep model, real-time three-dimensional images of anatomic landmarks were obtained, including the pulmonary veins and coronary sinus, which are of value in electrophysiological procedures. In vivo radio frequency ablation procedures in the right ventricle were also monitored, which yielded lesions of high image contrast.